Investigation on Processing Scheme for MIMO SAR with STSO Chirp Waveforms - Ye Kai; Yu Weidong; Wang Wei (Leida xuebao, 2017)
This study presents a novel processing scheme for Multiple-Input Multiple-Output (MIMO) Synthetic Aperture Radar (SAR) system with Short-Term Shift-Orthogonal (STSO) chirp waveforms to enhance its highresolution wide-swath mapping capability. Taking advantage of multi-beam digital beamforming techniques in elevation, the STSO chirp waveforms can be efficiently separated from mixed echo signals. According to the geometry model and the antenna architecture of MIMO SAR system, the modified multichannel reconstruction matrix is used to reconstruct the separated signals in azimuth. In addition, the reconstruction data can be imaged via conventional SAR algorithm. Simulation experiments are conducted on both point targets and distributed targets, the results of which indicate that the proposed scheme can effectively suppress the mutual interferences between the STSO waveforms and that it has good imaging performance.